To question about the essence cultural and linguistic competence (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The existence of the person's cultural-linguistic competence are proved in the article, as well as its components are considered here.
Keywords: language; culture; linguistic personality; jurisdiction